(untitled) (The International Journal for Scientific Research, 2024)
Design treatments play a major role in improving the quality of water when introducing pottery into its manufacture by using pottery treatment methods. Technological developments New techniques have emerged for the manufacture of water bottles, so the employment of pottery in the design treatments for this product crystallizes in a number of aspects, including aesthetic and others represented by environmental sustainability when making water bottles from it, as well as some design treatments according to the requirements of the current era represented in the ease of transportation for water bottles, based on the Therefore, the current research aimed to reveal the design treatments for water bottles using pottery in their manufacture, so in order to verify this goal, the researcher developed a mechanism for design treatments that resulted in some conclusions, the most important of which are: - Water consumption is daily and the need to take care of water bottles. - Plastic bottles are expensive and harmful to the environment.